208k views
1 vote
Simplify the following equations

Simplify the following equations-example-1
User Okkhoy
by
5.9k points

1 Answer

3 votes

Step-by-step explanation:

Given the expressions

1)


\sqrt[5]{16} * \sqrt[5]{2} \\= 16^(1/5) * 2^(1/5)\\= 2^(4(1/5)) * 2^(1/5)\\= 2^(4/5) * 2^(1/5)\\= 2^(4/5+1/5)\\= 2 ^(5/5)\\= 2^1\\= 2\\\\

2)


\frac{\sqrt[4]{243}}{\sqrt[4]{3}} \\= (243^(1/4))/(3^(1/4))\\= (3^(5/4))/(3^(1/4))\\=3^(5/4-1/4)\\= 3^(4/4)\\= 3

3)


(3+√(2) )(4+√(7) )\\= 3(4) + 3√(7) + 4√(2) + √(14) \\= 12 + 3√(7) + 4√(2) + √(14) \\

User Yeh
by
6.1k points